Combined Pancreas-Kidney Transplantation After Rescue Allocation: The Eurotransplant Experience: A Retrospective Multicenter Outcome Analysis - Assfalg, Volker; Stocker, Felix; Hüser, Norbert; Hartmann, Daniel; Matevossian, Edouard; van Bruchem, Milou; Vogelaar, Serge; Renders, Lutz; Schmaderer, Christoph; Margreiter, Christian; Deak, Andras; Messner, Franka; et al. (Transplantation, 2025)
Background. Simultaneous pancreas-kidney transplantation (SPKT) is the therapy of choice for selected patients with complicated type 1 diabetes mellitus and end-stage renal disease. Pancreas rescue allocation was implemented in Eurotransplant allocation algorithms to increase organ utilization, concurrently facilitating transplantation of supposedly inferior quality organs. The aim of this study was to examine whether outcomes of SPKT after rescue allocation, which can either be recipient-oriented extended allocation or competitive rescue allocation, were as good as after standard allocation. Methods. This retrospective multicenter analysis of 1504 SPKT performed from 2013 to 2021 evaluated outcomes by allocation type considering survival of patients, pancreas grafts, and kidney grafts. Multivariable analyses further explored the influence of specific donor-, recipient-, and transplant-related variables on outcomes. Results. Multivariable analyses showed no significant differences in SPKT outcome for standard allocation versus either rescue allocation type regarding patient, pancreas graft, and kidney graft survival. Rescue allocation organ donors were older, had higher body mass index, and were more likely to smoke. Rescue allocation had fewer HLA matches. Cold ischemic times of both pancreas and kidneys were longer in competitive rescue allocation but not in recipient-oriented extended allocation. Rescue allocation pancreas recipients had shorter waiting times. Multivariable analyses showed inferior pancreas and kidney graft survival for higher donor age. Higher recipient age correlated with higher mortality despite better pancreas graft survival. Conclusions. SPKT outcome after rescue allocation is comparable with standard allocation in both patient and graft survival. Age of both donors and recipients essentially influences the success of SPKT.
CRIS-Team Scopus Importer:2025-06-13